2019
DOI: 10.3390/ma12132108
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Metallo-Dielectric Structures: Electromagnetic Absorption and its Related Developed Temperatures

Abstract: Multi-layer, metallo-dielectric structures (screens) have long been employed as electromagnetic band filters, either in transmission or in reflection modes. Here we study the radiation energy not transmitted or reflected by these structures (trapped radiation, which is denoted—absorption). The trapped radiation leads to hot surfaces. In these bi-layer screens, the top (front) screen is made of metallic hole-array and the bottom (back) screen is made of metallic disk-array. The gap between them is filled with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…One is microwave heating technology, [2][3][4] which uses the energy absorbed from microwaves to generate and transfer thermal energy for specific applications. Prominent application scenarios include aircraft deicing, [5,6] medical microwave ablation therapy, microwave curing, [7][8][9][10] gas detection, [11][12][13][14] etc. The other is eliminating the effects of temperature rises resulting from the energy absorption, thereby improving the highpower processing capability of materials and enhancing their suitability for high-power applications.…”
Section: Introductionmentioning
confidence: 99%
“…One is microwave heating technology, [2][3][4] which uses the energy absorbed from microwaves to generate and transfer thermal energy for specific applications. Prominent application scenarios include aircraft deicing, [5,6] medical microwave ablation therapy, microwave curing, [7][8][9][10] gas detection, [11][12][13][14] etc. The other is eliminating the effects of temperature rises resulting from the energy absorption, thereby improving the highpower processing capability of materials and enhancing their suitability for high-power applications.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize though, that the effect in [3,4] is due to the lossy nature of the dielectric filler itself and less to do with the structured surface metal electrodes. We have shown that a bilayer structure can achieve 97% of absorption (A=0.97) in the near infrared without the necessity for a lossy dielectric material [12]. Here too, we do not include lossy dielectric material, though the conductor exhibits complex permittivity.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic metallo-dielectric structures (also known as screens, or metal meshes) have been studied in the past, and in particular in the long wavelength region -the wavelength region where the array pitch is of the order of, or smaller than the radiation wavelength [12,[14][15][16] -and thus, is above the diffraction region. Stacked periodic metal screens resemble photonic crystals with a large index of refraction ratio [17].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic radiation trapped within the bi-layer screens causes the temperature to rise rapidly. Walker et al [ 8 ] analysed the temperature distribution over time for different wavelengths of incident radiation when the structures are separated from the heat sink. In these bi-layer screens, the upper (front) screen is made of a metal grid of holes, and the lower (rear) screen is made of a metal disc grid.…”
mentioning
confidence: 99%